(untitled) - Dương, Thị Diễm Phúc (Can Tho, 2009)
This study aimed to investigate EFL learners' attitudes towards written errors, towards error correction, and towards teacher correction, peer correction and self-correction with teachers' help; and find out what type of correction learners perceived as the most favorable and efficient type to improve their writing accuracy and writing performance.
Keywords: English language,Tiếng Anh,English language,Tiếng Anh; Research,Nghiên cứu,Study and teaching,Dạy và học